Pembebanan Jaringan Jalan Dari Pintu Keluar Pelabuhan Bakauheni Dengan Adanya Jalan Tol Trans Sumatera - armanto, yogo nofian; heriyanto, dwi; karami, muhammad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
This research was conducted to determine the trip assignment or the selection of travel routes for vehicles coming out of Bakauheni Port with the existence of the Trans Sumatra Toll Road. The choice of route through the Trans Sumatra Toll Road by motorists will certainly affect the reduced travel time, where the travel value applies to each person is different. In this study, the data obtained using the Diversion Curve method with data analysis techniques model JICA 1, Multiplier Regression, and Logit-Binomial to determine the route selection model, and time value calculations using the PCI method. The results of this study indicate that the probability of vehicles switching to Trans Sumatra Toll Road for cars is 78.74%, trucks are 74.74%, and buses are 61.80%. Furthermore, the results of modeling route selection with diversion curves obtained in car vehicles are multiplier Regression models which means the greater the comparison of the time of using the toll road than using another alternative road the greater the percentage of vehicles switching to use the toll road and modeling of truck vehicle route selection and modeling of truck vehicle route selection is the Logit-Binomial model which means saving travel time is one of the reasons for driving trucks to use toll roads The calculation of the time value of the Trans Sumatra Toll Road is more economical compared to the Sumatra Highway.  Keywords: Trip assignment, vehicle probability, route selection, time value